THE DEVELOPMENT OF ANIMATION GAME-BASED LEARNING MEDIA IN HISTORY OF ISLAMIC CULTURE MATERIALS - Kulsum, Umi; Hadiyanto, Andy; Amaliyah, Amaliyah (Universitas Pendidikan Indonesia, 2022)
Abstract. This study aims to develop learning media of animated games in the subject of the History of Islamic Cultural, to determine product feasibility assessments from media experts, and teacher and student responses to media through questionnaires. This type of research is Research and Development (RD). The game is designed using the Construct 2 application. This research uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. This research produces learning media in the form of computer-based animation game applications. The results of the study concluded that the animated game learning media for the subject of the History of Islamic Cultural with material from the Umayyad Dynasty was in the “Very Good” category and was suitable for use.Keywords: Learning Media, Animation Game, History of Islamic Culture